Deep tillage and irrigation impacts on crop productivity of wheat in north-west India - DHALIWAL, JEEVANJOT; KAHLON, M.S.; KUKAL, S.S. (Journal of Soil and Water Conservation, 2022)
The coarse textured soils of the northwest India which are under rice-wheat cropping system are prone to subsurface compaction thereby restricts the root growth of wheat crop. A two year field (2016-17 and 2017-18) experiment was carried out to study the impact of deep tillage and irrigation regimes on productivity of wheat. The irrigation regimes were based on irrigation water to pan evaporation ratio of 1 (I1.0) and 0.5 (I0.5) and there were three tillage practices (1) conventional tillage in wheat-CT (2) Deep tillage before the sowing of wheat during the first season only-DT1 (3) Deep tillage before the sowing of wheat during both the crop seasons- DT2. Mean grain yield was significantly higher under DT1 (5.0 Mg ha-1) than CT (4.52 Mg ha-1) during 2016-17 and in 2017-18 it was highest in DT2 (5.19 Mg ha-1) followed by DT1 (4.96 Mg ha-1) and lowest in CT (4.79 Mg ha-1) tillage practices. Thus deep tillage attributed to higher grain yield that could be due to reduced penetration resistance under deep tilled conditions in comparison to conventional tillage which resulted in higher root growth and consequently the above ground biomass. However, the mean grain yield was lower under I0.5 irrigation regime than I1.0 irrigation regime during both the years.